PERANCANGAN DAN PEMBUATAN PERPUSTAKAAN DIGITAL IAIN IMAM BONJOL PADANG BERBASIS WEBSITE - veni wedyawati (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Library of State Islamic Institute ( IAIN ) Imam Bonjol Padang is a source of learning and intellectual resources are very important in its function as a service center information required by the academic in achieving program Higher Education , Library Information System which is running the manual or not using a computerized system. PHP is a multiuser software that can provide a solution to the problem lies at the top, where the software can be used in the manufacture of website designing websites at once. Keywords: System, Web, Design program